Migration of intrauterine device caused asymptomatic acute appendicitis: A case report - Zamani Bonab, Mehrangiz (Clin Case Rep, 2021)
Missing of IUD is not always due to expulsion. If the patient is sure that it has not got expulsed, further investigations such as abdominal ultrasound and X‐ray should be performed to look for the device before any device‐related complications.